Aplikasi Pemilihan Kaos Menggunakan Algoritma SAW dan TOPSIS - Waskito, Punto; Al Amin, Imam Husni (LPPM UNIKA Santo Thomas, 2023)
Fashion is a form of individual expression through clothing and accessories that are related to style and popular trends at a given time. The popularity of fashion is influenced by cultural, historical, social, political, and other factors. T-shirts have become the most common and versatile item in various fashion styles, both casual and formal. However, many people find it difficult to choose a suitable t-shirt that meets their needs and desires due to the many brand options available in Indonesia. Therefore, a decision support system is needed to help people choose the right t-shirt. This decision support system uses four criteria in selecting a t-shirt, namely material, design, sleeve, and size. This system adopts the Simple Additive Weighting (SAW) and Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) methods. The use of these two methods aims to obtain the best reference results from each method. The results from the SAW and TOPSIS methods have the same alternatives, namely A1 (Erigo - Antelope) and A7 (Elhaus - Guaranteed) with SAW ranking values of 0.96 and TOPSIS ranking values of 0.8235. The public can easily use the system because it is created as a website based on the PHP programming language and MySQL database.